The potentiation effect of Bawang Dayak (Sisyrinchium palmifolium L.) extract on T47D cell growth inhibition after 5-fluorouracil treatment - Yuniarti, Azizah; Sundhani, Elza; Nurulita, Nunuk Aries (Universitas Ahmad Dahlan, 2018)
5-Fluorouracil (5-FU) is chemotherapy agents that used in breast cancer treatment that has toxic effects such as myelotoxicity. its effectiveness relatively low. Bawang Dayak has been widely empirically used as a breast cancer treatment. This studys aims were to determine the sensitivity of 5-FU against T47D cells, as single and its combination with EBD, to determine apoptotic induction, and the inhibitory effect of T47D cell cycle. The cytotoxic assay was using the MTT method with the concetration of 5-FU (0-600Î¼g / mL) and EBD (0-250Î¼g / mL). Apoptotic induction analysis were determined by PI/annexin V. Both of apoptotic and cell cycle analysis was performed by flowcytometry. The results of the 5-FU and EBD cytotoxic test on T47D cells obtained IC50 274Î¼g/mL and 75Î¼g/mL, respectively. The combination of 5-FU and EBD has a mild to strong synergistic effect (CI 0.829 and 0.779). its ombined treatment induced apoptosis in T47D cells by 21.33%. Combination of these combinations caused cell accumulation in G0-G1 phase of 57.11%, greater than control (41.20%). Provision of 5-FU and EBD combination treatments causes disturbance and damage to cells that cause cell cycle arrest in the G0-G1 phase and can not proceed to the next phase. The combination of 5-fluorouracil and EBD has a synergistic effect as breast cancer co-chemotherapy is able to induce apoptosis against T47D cells by triggering cell accumulation in G0-G1 phase. The extract of Bawang Dayak has a high potential to be developed as co-chemotherapy in breast cancer.